Playing the Changes: Improvisation, Metaphor, and COVID-19 - Felepchuk, Erin; Finley, Ben (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Erin Felepchuk and Ben Finley examine the use of improvisation within the language of crisis response. They argue that historic cultural anxieties have generated negative connotations for improvisation within such conceptual metaphors as “illness as war” (where improvisation is positioned as a defensive strategy) and, more broadly, “improvisation as disorder,” and draw on improvisation studies theory and discourse to propose alternate metaphors for disease and disease mitigation.